Cognitive decline and white matter changes in mesial temporal lobe epilepsy. Issue 33 (August 2018) - Xu, Shang-wen; Xi, Ji-hui; Lin, Chen; Wang, Xiao-yang; Fu, Li-yuan; Kralik, Stephen Francis; Chen, Zi-qian
Abstract : Abstract: Noninvasive imaging plays a pivotal role in assessing the brain structural and functional changes in presurgical mesial temporal lobe epilepsy (MTLE) patients. Our goal was to study the relationship between the changes of cerebral white matter (WM) and cognitive functions in MTLE patients. Voxel-based morphometry (VBM) and tract-based spatial statistics (TBSS) MRI were performed on 24 right-handed MTLE patients (12 with left MTLE and 12 with right MTLE) and 12 matching healthy controls. Gray matter (GM), WM, and whole brain (WB) volumes were measured with VBM while fractional anisotropy (FA), mean diffusivity (MD), axial diffusivity (AD), and radial diffusivity (RD) were measured with TBSS. All patients and controls also underwent Montreal Cognitive Assessment (MoCA) before MRI. WM volume and the ratio of WM volume versus WB volume were significantly lower in MTLE patients compared with controls. WM volume in MTLE patients had a positive correlation with MoCA score ( r = 0.71, P < .001) and a negative correlation with the duration of epilepsy ( r = −0.693, P < .001). Volumetric differences were mainly located in the corpus callosum, uncinate fasciculus, inferior longitudinal fasciculus, and superior longitudinal fasciculus. FA of both left MTLE and right MTLE groups was significantly decreased, while MD, AD, and RD were significantly increased. Most left MTLE patients showed bilateral WM fiber tract changes versus ipsilateral changes for right MTLE patients. Changes in DTI parameters and WM volume were found in MTLE patients and more ipsilateral changes were seen with right-sided MTLE. Cognitive changes of MTLE patients were found to be correlated with the changes in WM structure. These findings not only provide useful information for lateralization of the seizure focus but can also be used to explain functional connectivity disorders which may be an important physiological basis for cognitive changes in patients with MTLE. Abstract : Supplemental Digital Content is available in the text